2010
DOI: 10.1186/1471-2202-11-118
|View full text |Cite
|
Sign up to set email alerts
|

Practice effects in healthy adults: A longitudinal study on frequent repetitive cognitive testing

Abstract: BackgroundCognitive deterioration is a core symptom of many neuropsychiatric disorders and target of increasing significance for novel treatment strategies. Hence, its reliable capture in long-term follow-up studies is prerequisite for recording the natural course of diseases and for estimating potential benefits of therapeutic interventions. Since repeated neuropsychological testing is required for respective longitudinal study designs, occurrence, time pattern and magnitude of practice effects on cognition h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
224
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(249 citation statements)
references
References 52 publications
16
224
1
Order By: Relevance
“…However, it is considered moderate in verbal fluency tasks [36] and especially in MS patients [18]. Moreover, it is worth noting that this effect is supposed to be more important during the first re-test than at subsequent evaluations [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is considered moderate in verbal fluency tasks [36] and especially in MS patients [18]. Moreover, it is worth noting that this effect is supposed to be more important during the first re-test than at subsequent evaluations [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, few placebo effects and PEs were reported during sham stimulation in hf-rTMS studies on healthy subjects [7] , AD [6] and PPA patients [9 , 10] . Moreover, PE is considered as moderate (<16%) especially in linguistic tasks (<5%) in healthy subject with high-frequency testing (2, 6 and 9 weeks and 3 months) [36] . Several studies have demonstrated that PE is largely absent in patients with neurodegenerative disease and dementia, even for short test-retest intervals [37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Order counterbalancing in typical pharmacological imaging studies effectively intermixes practice effects with drug order, and potentially modulates the brain-behavior effects researchers seek to identify. Although practice effects are well acknowledged in the broader DA and cognitive literatures (36)(37)(38), understanding of these effects is limited. DA is typically associated with various forms of learning (9,10,13,14,39), but data on how DA modulation interacts with practice remain sparse.…”
Section: Amph-related Relations Between Sd Bold and Wm Performance As Amentioning
confidence: 99%